Trauma Emosional pada Korban Kekerasan Verbal: Studi Kasus pada Remaja di Desa Tuntungan 1 - Ainul Mardiyah; Juli Rismayana Lubis; Icka Bella Sriwahyun; Nur Asia Sihombing (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
This study aims to describe the forms of emotional trauma experienced by adolescent victims of verbal violence in Tuntungan Village 1. The study used a qualitative approach with a case study method on three adolescents who were purposively selected based on their experiences of verbal violence in their family environment. Data collection techniques included in-depth interviews, participant observation, and documentation to obtain a comprehensive picture of the psychological condition of the research subjects. The obtained data were then analyzed descriptively qualitatively through the processes of reduction, presentation, and drawing conclusions. The results of the study indicate that verbal violence has a significant impact on the emotional health of adolescents, including decreased learning motivation, the emergence of withdrawal behavior from social environments, and the loss of a sense of security and comfort within the family. In addition, harsh, demeaning, and repetitive family communication patterns form a negative self-concept in adolescents, which has the potential to affect personality development and social relationships in the future. The findings of this study emphasize the important role of families, schools, and communities in creating a supportive environment, as well as the need for preventive efforts and psychosocial interventions to prevent and address emotional trauma in adolescents on an ongoing basis.